Interaction between calcium and some heavy metals in fish ponds that receive different water sources - Aly, Niema A. F.; Zenhom, M.M.; Al-Kenawy, D.A. (2009)
Agricultural drainage water source contains detectable amounts of different elements including calcium, phosphorus, nitrogen and some heavy metals (Cd, Cu, Fe, Pb and Zn) compared with irrigation water source. The present study aimed to investigate the effect of some elements e.g. calcium, phosphorus, nitrogen on fish reared in ponds receiving two different water sources. The study was conducted through two treatments with three replicates each. The first treatment was receiving agricultural drainage water source while the second one was receiving irrigation water (Nile water) source. Obtained results showed highly significant variation between the two treatments concerning some water parameters (total hardness, total alkalinity, light visibility, total ammonia, unionized ammonia, pH, dissolved oxygen, phosphorus and nitrate). Phytoplankton communities showed higher density in ponds of agricultural drain water compared with those of the irrigation water source. In addition, there were significant variations in the concentrations of Fe, Zn, Cu, Cd, Pb, and Ca in water supply, water ponds and fish flesh. We have demonstrated that the presence of C++ in water supply decreases the heavy metals residues in fish flesh. We concluded that there were negative correlation between Ca++ in fish muscle and water supply with heavy metals residues in fish muscles.
Includes reference.
Summary in Arabic.
1
Keywords: Water -- Pollution; Heavy metals -- Environmental aspects; Calcium -- Environmental aspects; Fish ponds; Heavy metals -- Environmental aspects